Complex systems and computational biology approaches to acute inflammation - An, Gary; Vodovotz, Yoram (Springer New York, 2013)
The Translational Dilemma, the difficulty in achieving effective translation of basic mechanistic biomedical knowledge into effective therapeutics, is the greatest challenge in biomedical research. Nowhere is this more apparent than in understanding and manipulating the acute inflammatory response in the settings of sepsis, trauma/hemorrhage, wound healing, and related processes. The burgeoning fields of complex systems analysis and computational biology offer researchers a pathway towards addressing the Translational Dilemma. Complex Systems and Computational Biology Approaches to Acute Inflammation presents the current state of the art of multi-disciplinary and systems-oriented research approaches to complex diseases arising from and driven by the acute inflammatory response. The chapters in this volume provide an introduction to different types of computational modeling, and how these methods can be applied to specific inflammatory diseases, with a focus on providing readers with a roadmap for integrating advanced mathematical and computational techniques with traditional experimental methods. By presenting the role of computational modeling as an integrated component of the research process, Complex Systems and Computational Biology Approaches to Acute Inflammation offers a window into the future of biomedical research.